Flexibility in Intercommodity Substitution May Sharpen Price Fluctuations - Mork, Knut Anton (Quarterly Journal of Economics, 1985)
Consider a competitive industry using an aggregate of two commodities as an input to production. Suppose that the supply of one of the commodities is stochastic. It can then be shown that investment in flexibility in the ex post choice among the two commodities is likely to result in a sharpening rather than dampening of the stochastic fluctuations in the aggregate commodity price if the supply elasticity is lower for the substitute commodity than for the one with stochastic supply. The paper derives this result and applies it to the case of ex post flexibility in fuel choice with uncertain fuel supply.